2011
DOI: 10.1140/epjb/e2011-20354-0
|View full text |Cite
|
Sign up to set email alerts
|

BCS-BEC crossover in mix-dimensional Fermi gases

Abstract: We investigate a mix-dimensional Fermi-Fermi mixture in which one species is confined in twodimensional(2D) space while the other is free in three-dimensional space(3D). We determine the superfluid transition temperature Tc for the entire BCS-BEC crossover including the important effects of noncondensed pairs. We find that the transition temperature reduces while the imbalance of mass is increased or lattice constant (dz) is reduced. In population imbalance case, the stability of superfluid is sharply destroye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In this paper we observed that the nontrivial topology of NC U (1) instantons faithfully appears in the emergent gravity description. For example, NC U (1) instantons give rise to the ALE-type four-manifolds [45,66] whose nontrivial topology is encoded in bolts (noncontractible two-cycles) while NC U (1) monopoles may be realized as the ALF-type four-manifolds whose nontrivial topology is encoded in nuts (isolated points). The nice formula (111) for the Euler characteristic clearly illuminates this aspect of four-manifolds emergent from symplectic (or NC) U (1) instantons or monopoles.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we observed that the nontrivial topology of NC U (1) instantons faithfully appears in the emergent gravity description. For example, NC U (1) instantons give rise to the ALE-type four-manifolds [45,66] whose nontrivial topology is encoded in bolts (noncontractible two-cycles) while NC U (1) monopoles may be realized as the ALF-type four-manifolds whose nontrivial topology is encoded in nuts (isolated points). The nice formula (111) for the Euler characteristic clearly illuminates this aspect of four-manifolds emergent from symplectic (or NC) U (1) instantons or monopoles.…”
Section: Discussionmentioning
confidence: 99%
“…From the gauge theory point of view, the symplectomorphisms can be identified with U (1) gauge transformations. 14,15,16 In other words, the gauge symmetry acting on U (1) gauge fields as A → A + dφ is generated by a Hamiltonian vector field X φ , i.e., satisfying ι X φ B + dφ = 0.…”
Section: Symplectization Of Spacetime Geometrymentioning
confidence: 99%
“…Hence, the final touch for the gauge/gravity duality is to find an explicit map between electromagnetism and gravity. 14,15,16 First, note that the U (1) gauge field (21) deforming an underlying symplectic structure is completely encoded into a local trivialization of the symplectic structure up to symplectomorphisms via the Darboux theorem or the Moser lemma. 17,18 Let us denote the local coordinate transformation φ : y µ → x µ (y) as…”
Section: Symplectization Of Spacetime Geometrymentioning
confidence: 99%
“…Note that, even for purely bosonic gases, the spatial overlap between bosons has been experimentally shown to be strongly suppressed by the strong correlations emerging in 1D [41]. In addition, mixed-dimensional systems allow to study interesting few-body [42] and manybody [22,43] phenomena. We should stress that the results reported here are relevant to several experimental realizations.…”
Section: Introductionmentioning
confidence: 99%